Crystal structure and electrical properties of Ag6PS5I single crystal - Studenyak Ihor; Студеняк Ігор; Pogodin Artem; Погодін Артем; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; Кохан Олександр; Symkanych Olesya; Симканич Олеся; Milan Timko; et al. (My University, 2021)
Abstract. The single crystals of quaternary halogen Ag6PS5I were grown from the solution–melt by means of a vertical zone crystallization method. The crystal structure has been ascertained using the Rietveld method. Investigation of electrical conductivity was carried out using the impedance spectroscopy technique within the frequency range 1·1013·105 Hz and temperature interval 293–383 K on gold contacts applied by chemical deposition from solution. Ionic (1.79·10–3 S/cm) and electronic (1.64·10–6 S/cm) components of electrical conductivity have been determined using the Nyquist plots. The mechanism of ionic conductivity for Ag6PS5I single crystal has been proposed which can be considered as ion diffusion through “channels” Ag2–Ag2.

Резюме. Методом вертикальної зонної кристалізації з розчину–розплаву вирощено монокристали тетрарного галогенхалькогеніду Ag6PS5I. Кристалічну структуру встановлено з використанням методу Рітвельда. Дослідження електричної провідності проведено з використанням методу імпедансної спектроскопії в частотному діапазоні 1·101–3·105Гц та температурному інтервалі 293–383 K на золотих контактах, нанесених методом хімічного осадження з розчину. За допомогою діаграм Найквіста визначено іонну (1.79·10–3 S/cm) та електронну (1.64·10–6 S/cm) складові електричної провідності. Запропоновано механізм іонної провідності в суперіонному провіднику Ag6PS5I, який можна розглядати як дифузію іонів крізь «канали» Ag2–Ag2.
Кристалічна структура та електричні властивості монокристала Ag6PS5I
Contents: http://journal-spqeo.org.ua/n1_2021/n1_2021_contents.htm Editorial board: http://journal-spqeo.org.ua/EditorialBoard.html
Keywords: argyrodite; superionic conductor; single crystal; impedance spectroscopy; electrical conductivity; crystal structure